Complicating and facilitating factors for revaluation of movable assets in public administration (Research, Society and Development, 2022)
The main purpose of the revaluation is to generate, on the part of the Public Administration, adjustments to the equity accounting procedures, in particular the measurement of assets at market value. The general objective of this research is to analyze the hindering and facilitating factors for the revaluation of movable assets at the Federal University of Sergipe. The study is qualitative, descriptive and uses the single case study method to understand and describe the employees' experience in the reassessment process. For data analysis, the content analysis technique was used. The result of the research identified the hindering and facilitating factors of the patrimonial survey and for the delimitation of the market value, in addition, subsidies were proposed for the process of revaluation of movable assets in a federal higher education institution, as required by ordinances 184/2008 of the Ministry of Finance and 548/2015 of the National Treasury Department. It was concluded that it is important to carry out a reliable asset survey and a physical inventory carried out with responsibility, that the large quantity and variety of UFS assets makes price and market research unfeasible for all the institution's assets, that a culture of reassessment not restricted to the commission and that the participation of civil servants in training courses should be encouraged.